Investigation on cutting of thin carbon fiber-reinforced polymer composite plate using sandwich electrode-assisted wire electrical-discharge machining. (October 2021) - Dutta, Hrishikesh; Debnath, Kishore; Sarma, Deba Kumar
This paper presents the experimental investigation on cutting of thin carbon fiber-reinforced polymer (CFRP) composite plate by wire electrical-discharge machining (WEDM) with the aid of sandwich assisting-electrodes. The difficulties such as incomplete cut and deviation in machining path during WEDM of CFRP were avoided by using metal plates (H13 steel) as assisting-electrodes. The spark initiation during WEDM of CFRP is difficult without exposing the carbon fiber as fibers are embedded into nonconductive polymer in CFRP. Thus, in this work, assisting-electrode was used to initiate the sparking without changing the surface integrity of the CFRP. The one-factor-at-a-time analysis was applied to study the effect of input parameters namely input current (2, 4, 6, 8, 10, and 12 A), pulse on time (10, 20, 30, 40, 50, and 60 µs), pulse off time (10, 20, 30, 40, 50, and 60 µs), and voltage (70 and 90 V) on the cutting time and the machined surface morphology. A decreasing trend was observed for cutting time with an increase in the current. Whereas, the cutting time was increased with an increase in the pulse off time. It was also observed that the cutting time initially increased with the pulse on time (10 to 30 µs) and then started decreasing with a further increase in the pulse on time (40 to 60 µs). The cutting time was significantly reduced at a higher level of voltage (90 V) when compared one-on-one with lower voltage level (70 V). In this study, microscopic analysis of the surface morphology was also extensively investigated which was not investigated earlier. The investigation showed damages such as breakage of carbon fibers, fiber-matrix debonding, and matrix cracking during WEDM of CFRP using sandwich assisting-electrode.